FEMALE PRESENCE IN THE MAIN STRUCTURE OF THE OLYMPIC MOUVEMENT - LEUCIUC Florin-Valentin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
The IOC has made women's participation in sporting activities and the Olympic Games - and by implication in administrative and sports authorities - one of its major concerns. At the same time, in 1994, the Olympic Charter was amended and now contains an explicit section on the need to work in this direction: (The IOC) "strongly encourages, by appropriate means, the promotion of women in sport at all levels and in all structures, particularly in the executive bodies of national and international sports organizations with a view to the strict application of the principle of equality of men and women" (Rule 2, paragraph 5).